2004
DOI: 10.1021/es049720m
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability and Chronic Toxicity of Zinc to Juvenile Rainbow Trout (Oncorhynchus mykiss):  Comparison with Other Fish Species and Development of a Biotic Ligand Model

Abstract: In this study, the effects of modifying Ca (0.2-4 mM), Mg (0.05-3 mM), Na (0.75-5 mM), and pH (5.5-7.5) on the chronic toxicity of zinc to juvenile rainbow trout (Oncorhynchus mykiss) were investigated using standard 30-d assays in which survival and growth were monitored. Survival was observed to be a more sensitive end point than growth, and mortality mainly occurred during the initial stages of the exposure. This suggested that the mode of action of zinc toxicity was mainly of an acute nature. A review and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
72
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 34 publications
5
72
0
Order By: Relevance
“…Also, Shetty Akhila et al (2007) reported that the determination of acute toxicity is usually an initial screening step in the assessment and evaluation of the toxic characteristics of all compounds. Likewise, De Schamphelaere and Janssen (2004) reported that fish mortality might be a more sensitive endpoint for assessing effect of Zn exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Also, Shetty Akhila et al (2007) reported that the determination of acute toxicity is usually an initial screening step in the assessment and evaluation of the toxic characteristics of all compounds. Likewise, De Schamphelaere and Janssen (2004) reported that fish mortality might be a more sensitive endpoint for assessing effect of Zn exposure.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the protective actions of Na + seemed to be similar in the chronic model and Janssen, 2004d). Furthermore, a chronic Zn-BLM has also been developed for fish (De Schamphelaere and Janssen, 2004c), and its similarity to the acute Zn-BLM in the dominant protective role of Ca 2+ in predicting mortality (the most sensitive endpoint in the chronic history) again suggest that the acute and chronic toxic mechanisms of zinc in fish are similar (i.e., disruption of Ca 2+ homeostasis). In case of silver also, the mechanism does appear similar (Na + balance pathology).…”
Section: +mentioning
confidence: 93%
“…For example, in toxicity tests with aquatic invertebrates incubated with lead-zinc mine tailings from the Tri-State mining district, Besser and Rabeni (1987) showed that increased concentrations of dissolved cadmium, lead, and zinc correlated with decreased survival and growth (Besser and Rabeni, 1987). Likewise, various fish species experienced rapid mortality when exposed to increasing dissolved zinc concentrations, but this effect decreased with increasing calcium, magnesium, and sodium concentrations (De Schamphelaere and Janssen, 2004). High metal concentrations in soils can also cause phytotoxicity.…”
Section: Ecological Health Concernsmentioning
confidence: 99%